Ligand Binding to Dynamically Populated G-Quadruplex DNA - Aznauryan, Mikayel; Noer, Sofie Louise; Pedersen, Camilla W; Mergny, Jean-Louis; Teulade-Fichou, Marie-Paule; Birkedal, Victoria (Chembiochem, 2021)
Several small-molecule ligands specifically bind and stabilize G-quadruplex (G4) nucleic acid structures, which are considered to be promising therapeutic targets. G4s are polymorphic structures of varying stability, and their formation is dynamic. Here, we investigate the mechanisms of ligand binding to dynamically populated human telomere G4 DNA by using the bisquinolinium based ligand Phen-DC3 and a combination of single-molecule FRET microscopy, ensemble FRET and CD spectroscopies. Different cations are used to tune G4 polymorphism and folding dynamics. We find that ligand binding occurs to pre-folded G4 structures and that Phen-DC3 also induces G4 formation in unfolded single strands. Following ligand binding to dynamically populated G4s, the DNA undergoes pronounced conformational redistributions that do not involve direct ligand-induced G4 conformational interconversion. On the contrary, the redistribution is driven by ligand-induced G4 folding and trapping of dynamically populated short-lived conformation states. Thus, ligand-induced stabilization does not necessarily require the initial presence of stably folded G4s.
Keywords: Fluorescence Resonance Energy Transfer; telomery; konformace nukleové kyseliny; chinoliny; G-kvadruplexy; Ligands; Molecular Dynamics Simulation; lidé; Quinolines; G-Quadruplexes; simulace molekulární dynamiky; Telomere; rezonanční přenos fluorescenční energie; Nucleic Acid Conformation; ligandy; Humans